Comparison of a physical-layer network coding system with iterative coding schemes - Al-Rubaie, Alaa A. S.; Tsimenidis, C. C.; Johnston, M.; Sharif, B. (2013 6th Joint IFIP Wireless and Mobile Networking Conference (WMNC), 2013)
Physical layer network coding (PNC) is a novel technique that allows two users to exchange messages in a wireless network. PNC takes place at a relay node and exploits the interference caused by incoming signals from the two users to increase throughput. In this paper, the performance of a two-way relay network employing PNC is evaluated with three types of error-correcting codes used at the source and destination nodes, namely low-density parity-check codes, turbo codes and bit-interleaved coded modulation with iterative decoding (BICM-ID). All three coding schemes perform similarly in a single user system on the AWGN channel with no relay, but results obtained when employing PNC show that although there is an overall degradation in their performance of all three codes, the LDPC code performance is more seriously affected due to the Sum-Product decoding algorithm being less robust to unreliable symbols broadcast from the relay.